The impact of the duration of untreated psychosis on the risk of involuntary hospitalization during the first psychotic episode - V. A. Chinarev (Медицинский вестник Юга России, 2025)
Objective: to assess the effect of untreated psychosis duration on the likelihood of involuntary hospitalization among patients with a first psychotic episode. Materials and methods: a retrospective analysis of data from patients admitted to inpatient treatment between 2020 and 2023 was conducted. Data was collected on the duration from the onset of the psychotic episode until hospitalization, as well as the reasons and circumstances leading to hospitalization, with clinical, psychopathological, and psychometric assessments of the patient's condition. Results: patients whose first episode of psychosis went untreated for more than 3 months were more likely to be hospitalized involuntarily compared to those who received treatment within the first month after symptom onset. Conclusions: the presence of destructive and autoaggressive behaviors, as well as gross psychoproductive symptoms and a high level of psychopathization, along with patient refusal of treatment increased the risk of hospitalization without consent. These findings emphasize the importance of early diagnosis and treatment for psychotic disorders, particularly in the case of a first episode. Early intervention can help reduce the risk of involuntary hospitalization and improve long-term treatment outcomes.